The chemistry of bread making: The role of salt to ensure optimal functionality of its constituents. Issue 3 (3rd April 2018) - Avramenko, N. A.; Tyler, R. T.; Scanlon, M. G.; Hucl, P.; Nickerson, M. T.
ABSTRACT: Large consumptions of dietary sodium have been shown to lead to hypertension, one of the main causative factors in cardiovascular disease. Bread (and other cereal products) accounts for ~30% of the overall sodium intake in our diet; therefore, industry has been developing strategies to significantly reduce its usage. However, at reduced sodium levels, dough handling can be affected due to sticky dough phenomena creating major processing issues and a poor quality final product. It is hypothesized that the formation of a strong gluten network plays a crucial role in developing nonsticky dough, a process that is strengthened in the presence of NaCl. However, at low NaCl levels, a weaker gluten network forms resulting in the prevalence of other wheat flours' constituents impact on water mobility within the dough to contribute to the stickiness phenomenon. This review discusses the underlying mechanisms that can influence the formation of sticky dough within a low sodium environment and discusses strategies used to help circumvent them.